Crystal structure of 3-(adamantan-1-yl)-4-methyl-5-{[(4-nitrophenyl)methyl]-sulfanyl}-4H-1,2,4-triazole, C20H24N4O2S - Al-Wahaibi, Lamya H.; Abdelbaky, Mohammed S. M.; Garcia-Granda, Santiago; Tiekink, Edward R. T. *; El-Eman, Ali A. (De Gruyter, 2022)
C20H24N4O2S, monoclinic, C2/c (no. 15), a = 28.5901(10) Å, b = 6.4383(4) Å, c = 20.060(1) Å, β = 99.682(4)°, V = 3639.9(3) Å3, Z = 8, R gt (F) = 0.0557, wR ref (F 2) = 0.1514, T = 150 K.